Once-monthly risedronate for postmenopausal osteoporosis - Kristina Casadei; Carolyn Becker (Dove Medical Press, 2009)
Kristina Casadei1, Carolyn Becker21Columbia University College of Physicians and Surgeons, New York, NY, USA; 2Brigham and Women’s Hospital, Division of Endocrinology, Diabetes, and Hypertension, Boston, MA, USAAbstract: Bisphosphonates are the mainstay of treatment for postmenopausal women with osteoporosis. Despite numerous clinical trials documenting efficacy, tolerability, and safety of bisphosphonate therapy, long-term persistence and adherence to these agents remains low. This has serious consequences for patients with osteoporosis in that medication non-compliance is associated with signifi cantly higher fracture risk. This review explores the unique physicochemical properties of bisphosphonates that allow more convenient intermittent dosing and whether less frequent dosing regimens improve compliance. Bisphosphonates are now available as oral drugs (taken daily, weekly, or monthly) or as intravenous preparations (given every 3 months or annually). The safety and efficacy of these various preparations are reviewed and compared, with particular emphasis on the newest agent to be approved, once-monthly risedronate. In contrast to monthly oral ibandronate, risedronate is the first and only monthly oral bisphosphonate to offer both vertebral and non-vertebral fracture reduction, based upon non-inferiority trials. Whether the greater convenience of this monthly oral bisphosphonate will translate into improved compliance and lower fracture risk is yet to be determined.Keywords: bisphosphonates, osteoporosis, monthly, risedronate, compliance